The Effectiveness of Using CIRC and CTL in Teaching and Learning Reading Comprehension - Dian Ismawati; Sugirin Sugirin (Universitas Negeri Yogyakarta, 2019)
Teaching reading in secondary level is aimed at teaching for comprehension. Comprehension occurs when the reader extracts and integrates various information from the text and combines it with what is already known. Reading comprehension is an intentional, active, interactive process that occurs before, during and after a person reads a particular piece of writing. When a person reads a text, he engages in a complex array of cognitive processes. In the teaching and learning process in SMP Negeri 1 Pecangaan, the teachers still dominate the activities. It emphasis on reading the text and then answers the questions based on the text and discussion to determine the correct answer. This is known as “Baca-Soal-Diskusi” technique (BSD). Concerned about the technique, the researcher thinks that the technique is not good enough. It can be seen that the students’ ability in understanding the text is not satisfactory enough. This research was aimed at describing(1) the difference of effectiveness between CIRC, CTLand conventional techniques and (2) which one is the most effective technique – CIRC, CTL, or conventional – in teaching and learning reading comprehension of grade VIII students of SMPN 1 Pecangaan.. This quasi experimental research used pretest posttest nonequivalent group design with teaching techniques as the independent variable and students’ reading comprehension as the dependent variable. The population of the research was the students of grade VIII of SMPN 1 Pecangaan in the academic year 2013/2014 with three classes were randomly chosen as the research sample. The data were gathered through pretest and posttest of students’ reading comprehension which were analyzed using Ancova continued by Scheffe test with the significance level of 0.05. The research results show that (1) There is a significant difference in the reading comprehension of the students taught using CIRC, that of those taught using the CTL, and that of those taught using the conventional technique with F = 3.68 and p = 0.03 (2) CIRC is the most effective technique among them with the sequence of effectiveness is CIRC followed by CTL and conventional technique. Keywords: CIRC technique, CTL technique, reading comprehension